Cultural Hybridization in Translation: Intrinsic and Extrinsic Dimensions in “Cerita dari Jakarta” - Widya Evayani; Yusuf Haikal; Arimbi Alessandra Naro (Center of Language Development, Institut Agama Islam Negeri Madura, 2025)
Cultural hybridization plays a significant role in shaping cross-cultural understanding. Nevertheless, research on how local ethnic identities are negotiated through translation remains limited, particularly regarding Betawi culture. This study examines the translation of Betawi cultural terms in Cerita dari Jakarta and its English version, Tales from Djakarta. Utilizing Homi K. Bhabha’s Third Space concept and Peter Newmark’s cultural categories, the study analyzes 257 pairs of cultural terms. Terms are categorized as hybridized when source cultural elements are retained, and as de-hybridized when adapted, generalized, or neutralized. The findings reveal that 63% of the terms are de-hybridized, indicating a tendency to prioritize communicative accessibility and narrative fluency for international readers. However, hybridization is predominant in material culture, especially in names and tangible cultural objects (92%), while idioms and ritual expressions are de-hybridized more frequently (5%). These results suggest that translation functions as a process of cultural negotiation, wherein local identities are selectively preserved or adapted for a global audience.